The DNA structure and sequence preferences of WRN underlie its function in telomeric recombination events - Edwards, Deanna N. (Nat Commun, 2015)
Telomeric abnormalities caused by loss of function of the RecQ helicase WRN are linked to the multiple premature ageing phenotypes that characterize Werner syndrome. Here we examine WRN's role in telomeric maintenance, by comparing its action on a variety of DNA structures without or with telomeric sequences. Our results show that WRN clearly prefers to act on strand invasion intermediates in a manner that favours strand invasion and exchange. Moreover, WRN unwinding of these recombination structures is further enhanced when the invading strand contains at least three G-rich single-stranded telomeric repeats. These selectivities are most pronounced at NaCl concentrations within the reported intranuclear monovalent cation concentration range, and are partly conferred by WRN's C-terminal region. Importantly, WRN's specificity for the G-rich telomeric sequence within this precise structural context is particularly relevant to telomere metabolism and strongly suggests a physiological role in telomeric recombination processes, including T-loop dynamics.